1992
DOI: 10.1007/bf00197263
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion map of Salla disease: attempts to localize the disease gene using a computer program

Abstract: Salla disease is a lysosomal storage disorder due to impaired transport of free sialic acid across the lysosomal membrane. The clinical presentation of this autosomal recessive trait is severe psychomotor retardation from early infancy on. In order to determine the gene locus for the disease we have initiated a genetic linkage study using polymorphic gene markers in representative family material comprising about 60% of all families known to be affected with Salla disease. Here we present an exclusion map base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In 1992, Haataja and coworkers conducted a genetic linkage analysis of 24 families, where at least one member had SD. They studied 64 gene markers on 19 autosomes by exclusion mapping and concluded that chromosome 2q was a likely candidate site for the disease gene (Haataja et al, 1992). However, extended analysis using 85 restriction fragment length polymorphisms (RFLP) and 86 microsatellite markers provided evidence that the SD gene mapped to the long arm of chromosome 6.…”
Section: Chromosome 6qmentioning
confidence: 98%
“…In 1992, Haataja and coworkers conducted a genetic linkage analysis of 24 families, where at least one member had SD. They studied 64 gene markers on 19 autosomes by exclusion mapping and concluded that chromosome 2q was a likely candidate site for the disease gene (Haataja et al, 1992). However, extended analysis using 85 restriction fragment length polymorphisms (RFLP) and 86 microsatellite markers provided evidence that the SD gene mapped to the long arm of chromosome 6.…”
Section: Chromosome 6qmentioning
confidence: 98%